2017
DOI: 10.3233/jad-170032
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Amyloid-β Levels are Increased in Patients with Insomnia

Abstract: Previous studies demonstrate that patients with sleep disorders are at risk of developing Alzheimer's disease (AD), with the mechanism unknown. It is suggested that acute sleep deprivation induces an increase of amyloid-β (Aβ), the major pathological agent in AD, in the cerebrospinal fluid (CSF). In the present study, we recruited 23 patients with chronic insomnia aged between 46 to 67 years and 23 healthy controls aged between 43 to 67 years. We investigated the CSF levels of Aβ and tau, another pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…Aβ is considered as the major pathological agent of AD. It is demonstrated that insomnia can lead to an increase in the levels of Aβ of CSF and this Aβ can cause synaptic dysfunction and neurotransmission impair, essential mechanisms to the pathogenesis of AD [51,56]. Also, sleep impairment can lead to:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aβ is considered as the major pathological agent of AD. It is demonstrated that insomnia can lead to an increase in the levels of Aβ of CSF and this Aβ can cause synaptic dysfunction and neurotransmission impair, essential mechanisms to the pathogenesis of AD [51,56]. Also, sleep impairment can lead to:…”
Section: Discussionmentioning
confidence: 99%
“…Aβ is considered as the major pathological agent of AD. It is demonstrated that insomnia can lead to an increase in the levels of Aβ of CSF and this Aβ can cause synaptic dysfunction and neurotransmission impair, essential mechanisms to the pathogenesis of AD [ 51 , 56 ]. Also, sleep impairment can lead to: Induction of the extracellular release of tau [ 129 , 159 ] which this increase can result in neurodegeneration and neuron loss and can explain the association of insomnia to AD pathogenesis [ 53 , 95 , 160 , 161 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor sleep quality, which is associated with dementia, might negatively affect the activity of the glymphatic system [ 340 ]. CSF levels of Aβ have been found to be increased significantly in insomnia patients [ 361 ]. Thus, the role of the glymphatic system in AD with regards to Aβ may be that its decreased activity leads to impaired AβO clearance, which may lead to further aggregation resulting in larger AβOs or insoluble amyloid plaques, both of which the glymphatic system cannot clear.…”
Section: Trending Topics In Aβo Researchmentioning
confidence: 99%
“…Specific disruption of SWA in healthy adults without sleep disorders correlated with an increase in Aβ [91]. In patients with insomnia CSF Aβ levels were significantly higher than in healthy controls [92].…”
Section: Amyloid-β and Sleepmentioning
confidence: 99%